Breakup effects on alpha spectroscopic factors of 16O. (5th December 2016) - Adhikari, S; Basu, C; Sugathan, P; Jhinghan, A; Behera, B R; Saneesh, N; Kaur, G; Thakur, M; Mahajan, R; Dubey, R; Mitra, A K
Abstract: The triton angular distribution for the 12 C( 7 Li, t) 16 O* reaction is measured at 20 MeV, populating discrete states of 16 O. Continuum discretized coupled reaction channel calculations are used to to extract the alpha spectroscopic properties of 16 O states instead of the distorted wave born approximation theory to include the effects of breakup on the transfer process. The alpha reduced width, spectroscopic factors and the asymptotic normalization constant (ANC) of 16 O states are extracted. The error in the spectroscopic factor is about 35% and in that of the ANC about 27%.